Application of Guided Inquiry Learning Model Towards Science Process Skills - Nurlina Nurlina (Universitas Muhammadiyah Makassar, 2020)
The main problem in this study is whether there are differences in the science process skills of students after the guided inquiry learning model is applied. This study aims to determine whether there are differences in science process skills of students after applying the guided inquiry learning mode. This type of research is pre-experimental and One Group Pretest-Posttest Design research design. The population in this study were all students of class XI IPA of SMA Negeri 4 Binongko in the academic year 2019/2020, amounting to 30 students consisting of one class, so that the population mentioned above as well as research samples. The research instrument used was a science process skills test. The results of descriptive analysis on the pretest obtained an average score of 8.84 scientific process skills baseline while in the posttest obtained an average score of science process skills of 16.35 with a normalized gain index of 0.47 which included the medium category. Based on these results, it can be concluded that learning using the guided incutri learning model provides a better influence in improving students' science process skills. As for suggestions so that the implementation of the guided inquiry learning model implemented optimally it is necessary to manage time appropriately so that the learning objectives can be achieved.Keywords: Guided Inquiry Learning Model, Science process skills.Masalah utama dalam penelitian ini adalah apakah terdapat perbedaan keterampilan proses sains peserta didik setelah diterapkan model pembelajaran inkuiri terbimbing. Penelitian ini bertujuan untuk mengetahui apakah terdapat perbedaan keterampilan proses sains peserta didik setelah diterapkan model pembelajaran inkuiri terbimbing. Jenis penelitian ini adalah pra-eksperimen dan desain penelitian One Group Pretest-Posttest Design. Populasi dalam penelitian ini adalah seluruh peserta didik kelas XI IPA SMA Negeri 4 Binongko tahun ajaran 2019/2020 yang berjumlah 30 peserta didik terdiri dari satu kelas, sehingga populasi tersebut di atas sekaligus sebagai sampel penelitian. Instrumen penelitian yang digunakan berupa tes keterampilan proses sains. Hasil analisi deskriptif pada pretest diperoleh skor rata-rata keterampilan proses sains sebasar 8,83 sedangkan pada posttest diperoleh skor rata-rata keterampilan proses sains sebesar 16,35 dengan indeks gain ternormalisasisebesar 0,47 yang termasuk kategori sedang. Berdasarkan hasil penelitian tersebut, dapat disimpulkan pembelajaran menggunakan model pembelajaran inkuiri terbimbing memberikan pengaruh yang lebih baik dalam meningkatkan keterampilan proses sains peserta didik. Adapun saran agar penerapan model pembelajaran inkuiri terbimbing terlaksana dengan optimal perlu melakukan pengelolaan waktu secara tepat sehingga tujuan pembelajaran dapat tercapai.Kata kunci: Model Pembelajaran Inkuiri Terbimbing, Keterampilan proses sains